Analyses of pedestrian behavior on mid-block unsignalized crosswalk comparing Chinese and German cases. (4th November 2015) - Jiang, Xiaobei; Wang, Wuhong; Bengler, Klaus; Guo, Weiwei
A large number of pedestrian fatalities are caused by the vehicle-pedestrian accidents. The application of new theory and technological approaches may hold great potential to reduce the accident frequency and severity for pedestrians. Considered the different driving cultures between China and Germany, the adaptation of such application in new market triggers an "intercultural comparison" related to the road user behavior and traffic safety. Field traffic data have been collected by video recording and image processing at unsignalized mid-block crosswalks both in Beijing, China and Munich, Germany. Centered Vehicle-Pedestrian conflict situation, pedestrian speed performance in different pedestrian categories and walking phases, pedestrian waiting behavior related to waiting decision choice and waiting time, pedestrian gap acceptance were statistically analyzed for understanding the pedestrian behavior in the conflict process. Intercultural comparisons were made between China and Germany. The research results addressed how the conflict participants (pedestrians only) behave differently and would hopefully be the impetus for further intercultural analyses from urban traffic side.